INNOVATIVE APPROACHES TO IMPROVING STUDENTS’ PROFESSIONAL METHODOLOGICAL COMPETENCES BASED ON DIGITAL EDUCATIONAL TECHNOLOGIES - Murodova Khilola Umarkulovna; Ibroyimova Bahor Iskandar qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This work studies innovative approaches to the formation and development of students’ professional methodological competencies based on digital educational technologies. Today, the global digitalization process requires the widespread introduction of new technologies in the education system. Especially in the field of vocational education, modern digital platforms, virtual laboratories, interactive training, online courses and educational tools based on artificial intelligence play an important role in the development of students’ knowledge and skills. The study analyzes the possibilities of using digital tools to help students acquire practical skills in their professional activities faster and more effectively, develop independent learning and critical thinking skills. Also, information is provided on personalized education, adaptive learning systems, gamification, AR augmented reality and VR virtual reality technologies, and blockchain-based certification systems as innovative approaches.